2007
DOI: 10.1128/jvi.01720-06
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-Independent Major Histocompatibility Complex Class I Cross-Presentation Mediated by Papaya Mosaic Virus-Like Particles Leads to Expansion of Specific Human T Cells

Abstract: The development of versatile vaccine platforms is a priority that is recognized by health authorities worldwide; such platforms should induce both arms of the immune system, the humoral and cytotoxic-Tlymphocyte responses. In this study, we have established that a vaccine platform based on the coat protein of papaya mosaic virus (PapMV CP), previously shown to induce a humoral response, can induce major histocompatibility complex (MHC) class I cross-presentation of HLA-A*0201 epitopes from gp100, a melanoma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 44 publications
3
49
0
1
Order By: Relevance
“…PapMV-like particles displaying the immunodominant p33 CTL epitope from LCMV are internalized by DCs and cross-presented to specific CTLs. We recently reported that this is achieved through a proteasome-independent pathway (14), as shown for another VLP-based system (30). Importantly, and in contrast to many VLPs described so far, PapMV-like particles directly prime protective CTL responses in vivo without an adjuvant (i.e., CpGs or anti-CD40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PapMV-like particles displaying the immunodominant p33 CTL epitope from LCMV are internalized by DCs and cross-presented to specific CTLs. We recently reported that this is achieved through a proteasome-independent pathway (14), as shown for another VLP-based system (30). Importantly, and in contrast to many VLPs described so far, PapMV-like particles directly prime protective CTL responses in vivo without an adjuvant (i.e., CpGs or anti-CD40).…”
Section: Discussionmentioning
confidence: 99%
“…PapMV VLPs, formed by the self-assembly of the CP after overexpression in Escherichia coli (39), can carry foreign epitopes and induce the production of specific antibodies in vaccinated mice (7). Moreover, we have recently shown that a human B-cell line can cross-present CTL epitopes displayed on PapMV VLPs to specific T cells in vitro in a proteasome-independent fashion (14). To determine whether such VLPs could also trigger the development of protective cellular immunity in vivo, PapMV VLPs carrying the H-2 b -restricted dominant p33 CTL epitope from LCMV (PapMV-p33 VLPs) were engineered and evaluated for the capacity to induce CTL responses against LCMV.…”
mentioning
confidence: 99%
“…Vaccination with such nanoparticles generates a specific cellular and humoral immune response against displayed Ags and provides protection against various viral infection models (19,(22)(23)(24)(25). Moreover, we have demonstrated that the fused Ags are efficiently cross-presented on MHC class I of human APCs and cause the expansion of human Ag-specific T cells (26). Finally, we recently showed that PapMV used as an immunomodulator leads to the development of protective immune responses against influenza or Streptococcus pneumoniae challenges (27).…”
mentioning
confidence: 96%
“…Monocyte-derived dendritic cells (DC) were generated from PBMCs of healthy donors (35), followed by 24 h of stimulation with 500 ng/ml soluble trimeric CD40L (Immunex) and/or 10 3 U/ml IFN-␥ (Pierce Endogen) and/or 5 g/ml LPS (Sigma-Aldrich).…”
Section: Cells and Reagentsmentioning
confidence: 99%